Determinan of the Effects of Economic Factors on Informal Sector Labors: A Study of Java Island - Virgilius Christyomukti; Bahtiar Fitanto (Journal of Development Economic and Social Studies, 2026)
The informal sector persists as a critical challenge in labor market dynamics across developing countries, including Indonesia. Despite experiencing multiple economic cycles, the proportion of informal workers on Java Island consistently exceeded 50 percent during the 2017-2024 period, reflecting low productivity, limited social protection, and the loss of potential government tax revenues. This study examines the effects of Provincial Minimum Wage, GDP per capita, and educational attainment on informal employment across six provinces on Java Island from 2017 to 2024. Using Fixed Effect Model panel data regression, the analysis reveals that minimum wage regulations significantly increase informal sector participation, while economic growth significantly reduces it. Educational attainment, however, shows no significant effect on informal employment patterns. These findings validate Hernando de Soto's institutional theory linking regulatory burdens to informality and support Fei-Ranis structural transformation theory positioning economic growth as the driver of labor formalization. The insignificance of education is driven by several factors, primarily because the informal sector does not require formal educational qualifications as entry barriers, allowing workers with varying educational backgrounds to participate equally. Additionally, poor educational quality fails to equip workers with competencies that differentiate them for formal sector opportunities, creating a structural misalignment where education loses its market signaling value. Policy implications emphasize productivity-indexed minimum wage determination, accelerated inclusive economic growth, and educational reform addressing quality enhancement and labor market alignment to reduce informal employment dependency and improve worker welfare.